Response of Water Cherenkov Detectors to Small Signals: a Case Study - Thao, Nguyen Thi; Diep, Pham Ngoc; Dong, Pham Ngoc; Nhung, Pham Thi Tuyet; Darriulat, Pierre; Anh, Pham Tuan; Hoai, Do Thi (Communications in Physics, 2013)
Detailed studies of the response of the VATLY water Cherenkovdetector, a replica of those used in the ground array of the PierreAuger Observatory, are presented with emphasis on the response to lowamplitude signals. The method used is to detect decay electrons frommuons stopping in the water volume. Results include properties of the detection process as well as of the atmospheric cosmic ray flux.